If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + 12p = -5 Combine like terms: p + 12p = 13p 13p = -5 Solving 13p = -5 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Divide each side by '13'. p = -0.3846153846 Simplifying p = -0.3846153846
| 2(3p+1)=8(4+p) | | 3=12-3r | | 31=z-12 | | 31=z-12 | | 204=90x+80x | | 3.954+26.7= | | 10y+29-8y=5y+5 | | 6(x-3)=3(x+2)+27 | | 10+200= | | 4-4a=-(1+3a) | | 4w+w-26=19 | | 13u=-42 | | 0.75z=0.25z+12 | | 40=9x+8x | | 12+3(-7x-6)+13x=121 | | 9+4w/10=12/7 | | 3.95x+26.7= | | (x+1)(3x-2)=78x^2 | | z+-73=-4 | | x+.054=-1.802 | | 4v=-12 | | y^2-13x=-30 | | h-15=-11 | | 3x+22.5= | | 300+0.70(1300)= | | W=lw | | y^2+9y=36 | | 2(2b-3)+4b-5=53 | | (4a+8b)(3a+2b)= | | 32x-16=0 | | -6-3(x-7)=-2(-2x-4) | | 3(3x-4)-5(x+6)=107 |